1996
DOI: 10.1152/ajpgi.1996.270.5.g778
|View full text |Cite
|
Sign up to set email alerts
|

5-HT released by mucosal stimuli initiates peristalsis by activating 5-HT4/5-HT1p receptors on sensory CGRP neurons

Abstract: The intestinal peristaltic reflex can be elicited by mucosal stimulation or circular muscle stretch. Muscle stretch activates extrinsic, whereas mucosal stimulation activates intrinsic calcitonin gene-related peptide (CGRP)-containing sensory neurons. The present study examined the role of 5-hydroxytryptamine (5-HT) in sensory transmission. A three-compartment preparation of rat colon was used that enables separate measurement of sensory transmitters and modulators. Mucosal stimuli (2-8 brush strokes) caused c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
199
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(218 citation statements)
references
References 0 publications
13
199
1
1
Order By: Relevance
“…In fact, 5-HT3 and 5-HT4 receptors are crucial in the regulation of intestinal motility and the peripheral peristaltic reflex. This action is performed by the release of serotonin by enterochromaffin cells to intrinsic and extrinsic efferent neurons [20,23,[29][30][31] (Fig. 2).…”
Section: Serotonin Synthesis and Physiologymentioning
confidence: 99%
“…In fact, 5-HT3 and 5-HT4 receptors are crucial in the regulation of intestinal motility and the peripheral peristaltic reflex. This action is performed by the release of serotonin by enterochromaffin cells to intrinsic and extrinsic efferent neurons [20,23,[29][30][31] (Fig. 2).…”
Section: Serotonin Synthesis and Physiologymentioning
confidence: 99%
“…5-HT might also be secreted by endocrine cells and act as a hormone or through activation of local neural pathways. Numerous studies revealed that 5-HT was released in response to pressure, mucosal stimuli from the intestinal mucosa and evoked peristaltic or secretory reflexes (Kirchgessner et al, 1992;Grider et al, 1996;Zhu et al, 2001;Bertrand, 2007;Patel et al, 2007).…”
Section: -Ht and Tachykinin In The Rabbit Ileummentioning
confidence: 99%
“…Numerous pharmacological studies have provided evidence that 5-HT can act on the secretion of intestinal fluid and electrolytes (Bjorck et al, 1988) and gastrointestinal motility (Grider et al, 1996;Wade et al, 1996;Bush et al, 2001). In guinea pig, morphological studies described a rich, varicose 5-HT-immunoreactive (IR) fiber network in the myenteric and submucous plexuses and reactive nerve cells with short, broad dendrites and a single long process in the myenteric plexus (Costa et al, 1982).…”
mentioning
confidence: 99%
“…The released Ach and CGRP excite the ascending and descending interneurons, which in turn release Ach at their terminals. Presynaptic 5HT4 receptors also augment this Ach release (Grider 1996;Gershon 2004Gershon , 2005. The ascending interneurons synapse with excitatory motor neurons cephalad to the site of stimulus (bolus), which release Ach and substance P. This results in smooth muscle contraction cephalad to the bolus.…”
Section: Enteric Nervous System Serotonin and Serotonin Receptorsmentioning
confidence: 99%
“…This whole process results in propagation of the bolus in a coordinated fashion. 5HT1p receptors play a key role in the initiation of peristalsis, whereas 5HT4 receptors play a role in augmenting the release of neurotransmitters once the process is initiated by 5HT1p receptor stimulation (Grider 1996;Gershon 2004Gershon , 2005. 5HT3 receptors are found on the terminals of extrinsic afferent neurons, and are involved in the transmission of sensory stimuli to the CNS.…”
Section: Enteric Nervous System Serotonin and Serotonin Receptorsmentioning
confidence: 99%